Marsupial Genetics and Genomics - Waters, Paul D.; Waters, Paul D.; Deakin, Janine E.; Deakin, Janine E.; Marshall Graves, Jennifer A.; Marshall Graves, Jennifer A. (Springer Netherlands : Imprint: Springer, 2010)
Marsupials belong to the Class Mammalia, sharing some features with other mammals, yet they also possess many unique features. It is their differences from the more traditionally studied mammals, such as mice and humans, that is of greatest value to comparative studies. Sequencing of genomes from two distantly related marsupials, the short grey-tailed opossum from South America and the Australian tammar wallaby, has launched marsupials into the genomics era and accelerated the rate of progress in marsupial research. With the current worldwide concern for the plight of the endangered Tasmanian devil, marsupial genetics and genomics research is even more important than ever if this species is to be saved from extinction. This volume recounts some of the history of research in this field and highlights the most recent advances in the many different areas of marsupial genetics and genomics research.